Rio, Tokyo Paralympic Games and beyond: How to Prepare Athletes with Motor Disabilities for Peaking - Thomas W. J. Janssen (Frontiers Research Topics, 2017)
In 1960, the 9th Annual International Stoke Mandeville Games were supported, for the first time, by the Italian Olympic Committee. Taking place six days after the Closing Ceremony of the XVII Olympic Games, the paralympic games for disabled athletes were born. From Roma in 1960 to London in 2012, the Paralympic Games grew in terms of athletes' number from 400 to 4,237, and now brings together more than 164 nations (Perret, 2015). The word "Paralympic" derives from the Greek preposition "para" (beside or alongside) and the word "Olympic". Paralympics want to be the parallel Games to the Olympics and illustrate how the two movements exist side-by-side (Paralympics - History of the Movement, 2016). Now taking place after the Olympics Games, the Paralympic Games are the pinnacle of the career of athletes with physical impairments and have become the second largest sport event in the world (Perret, 2015; Paralympics - History of the Movement, 2016; Gold and Gold, 2011). The first statement of the vision of the International Paralympic Committee (IPC), i.e. "to create the conditions for athlete empowerment through self-determination" (Paralympics - History of the Movement, 2016; International Paralympic Committee, 2016), shows the importance of the place of the athlete with an impairment at the heart of the Paralympic Movement. The ultimate aim of the IPC is « to enable Paralympic athletes to achieve sporting excellence and inspire and excite the world. » (International Paralympic Committee, 2016). The performance level of athletes with an impairment improved to a point that, in the present days, sport news and world sport movements focus on the potential advantage of artificial limbs among athletes with amputations and their integration in able-bodied competitions (Burkett, 2010). However, they do not represent the totality of athletes with an impairment at the Paralympic Games. Athletes with other physical impairments (visual deficit, spinal cord injury, cerebral palsy or else) are eligible to compete. These impairments induce typical functional and physiological (e.g., cardiovascular, thermoregulatory) responses to exercise. For example, spinal cord injury (athletes with tetraplegia or paraplegia) causes thermoregulatory impairment (Goosey-Tolfrey et al., 2008) and individuals with cerebral palsy have also demonstrated higher thermal and metabolic strain than matched controls during treadmill walking in the heat (Maltais et al., 2004). Thus, hyperthermia among these athletes with an impairment alters their performance compared to their Olympic counterparts (Bhambhani, 2002). Mechanical performance analysis, the description of physiological responses according to the functional impairment or else the response to training and the relationship between laboratory and field testing responses are different parts of a package introduced here to address the aim of the IPC: to enable Paralympic athletes to achieve sporting excellence (Paralympics - History of the Movement, 2016; International Paralympic Committee, 2016).